(untitled) (Baghdad Science Journal, 2018)
In this work Aquatic plant (Nile rose) was used to study adsorption of industrial dye (safranin-O from aqueous solution within several operation conditions. The dried leaves of Nile rose plant were used as adsorbents safranin-O from aqueous solution after different activations such as wet and dry enhancements. The data show increasing in dye solution removal percentage for both activation methods of the adsorbent and also dye removal percentage that was obtained by using adsorbent without any treatment with the progress contact time. The dye removal percentages at equilibrium time 40 minutes were 88.7% at non-activation, 92.3% at thermal activation, and 98.3% at acidic activation. The samples adsorbents before and after adsorption which were scanned by using Fourier Transform Infrared (FTIR) Spectrometry. The scan data showed that the adsorbents contained hydroxyl group in there structure of adsorbents.